Determination Tourism Village Economy: Does Covid-19 Have An Impact On Pades And Village Community Income? - Devi Febrianti; Suryani Yuli Astuti (Jurnal Akademi Akuntansi, 2023)
Purpose: This research was developed to analyze the things that can determine the economy of a tourism village affected by Covid-19 in Lamongan Regency in terms of PADes and Village Community Income.